Administrative Innovation versus the Principle of Legality: Towards a Balanced Legal Model for the Protection of the Public Interest - Zaidan Qasim, Assist. Lect. Ali; Fawzi Youssef, Lect. Dr. Emad (Basra studies journal, 2026)
This study examines the relationship between administrative innovation and the principle of legality within the framework of administrative law, in light of the rapid transformations affecting modern public administration. Administrative innovation has become an urgent necessity for improving the performance of public utilities and enhancing the quality of public services, whereas the principle of legality requires public administration to remain subject to the law and to refrain from any abuse of power. The research analyzes the legal concepts of administrative innovation and the principle of legality, explores the areas of tension and complementarity between them, and highlights the legal challenges that hinder achieving a balance between administrative development and legal compliance. It also examines the role of the administrative judiciary and legal doctrine in consolidating this balance. Ultimately, the study proposes a balanced legal model that ensures legitimate administrative flexibility while safeguarding the public interest within the framework of the rule of law.